The encounter of Eastern Christianity with early Islam - Grypeou, Emmanouela.; Swanson, Mark; Thomas, David 1948- (The history of Christian-Muslim relations,, 2006)
The theme of this book is the early encounters between Christianity and Islam in the eastern provinces of the Byzantine Empire and in Persia from the beginnings of Islam in Mecca to the time of the Abbasids in Bagdad. The contributions in this volume deal with crucial subjects of political and theological dialogue and controversy that characterized the varying responses of the Christian communities in the Byzantine Eastern provinces to the Islamic conquest and its subsequent impact on Byzantine society and history. This volume opens up new research perspectives surrounding the confrontation of Christianity with the early theological and political development of Islam. The present publication emphasizes the importance of the study of the beginnings and the foundations of the relations between the two religions.